Kajian Interkoneksi untuk Sistem Pembangkit Listrik Tenaga Surya On-Grid - Halim, Levin (Website, 2023)
As an alternative source of green and renewable energy, a Solar Power Plant can be installed that utilizes solar cells. On-grid PV is one of the easiest types of PV systems to implement because it does not use batteries, but requires interconnection with the grid network system to run properly. On-grid PV interconnection requires technical study to review the impact of On-grid PV interconnection to the grid system and to review its compliance with the applicable Grid Code. Interconnection technical study consists power flow analysis, short circuit analysis, harmonic analysis, and transient stability analysis. The case study of the 7kW On-Grid PLTS installation is reviewed in this study, and the results of this technical study recommend that the On-Grid PLTS installation is feasible to operate and fulfills all the Grid-Code rules.